2020
DOI: 10.1159/000510294
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Simulated Workday of Prolonged Sitting on Seated versus Supine Blood Pressure and Pulse Wave Velocity in Adults with Overweight/Obesity and Elevated Blood Pressure

Abstract: We evaluated the effects of a simulated workday of prolonged sitting on blood pressure (BP) and pulse wave velocity (PWV) and examined whether posture (seated vs. supine) affected responses. Participants (n = 25) were adults, with overweight/obesity and elevated BP, and performed seated desk work for 7.5 h. BP and PWV were measured in seated and supine postures at baseline (7:15 a.m.), midday (12:05 p.m.), and afternoon (4:45 p.m.). Generalized linear mixed models evaluated the effects of prolonged sitting on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Across postures, we calculated an agreement of ICC = 0.77 (95%CI: 0.63-0.86) for cfPWV measurements made in supine and seated postures. In a separate study, carotid-radial (cr) PWV and carotid-ankle (ca) PWV were measured in the seated and supine postures prior to and following 7.5 h of sitting in 25 middle-aged adults (42 [SD: 12] years) (69). We again found a posture effect, with higher crPWV (β = 0.43 m/s, standard error [SE: 0.13], p = 0.001) and caPWV (β = 2.04 [SE: 0.17] m/s, p = 0.001) in the seated posture, but no posture by time interaction effect.…”
Section: Pulse-wave Velocitymentioning
confidence: 99%
“…Across postures, we calculated an agreement of ICC = 0.77 (95%CI: 0.63-0.86) for cfPWV measurements made in supine and seated postures. In a separate study, carotid-radial (cr) PWV and carotid-ankle (ca) PWV were measured in the seated and supine postures prior to and following 7.5 h of sitting in 25 middle-aged adults (42 [SD: 12] years) (69). We again found a posture effect, with higher crPWV (β = 0.43 m/s, standard error [SE: 0.13], p = 0.001) and caPWV (β = 2.04 [SE: 0.17] m/s, p = 0.001) in the seated posture, but no posture by time interaction effect.…”
Section: Pulse-wave Velocitymentioning
confidence: 99%
“…After reading the full text of the remaining articles and rescreening, a total of 163 documents were excluded (non-original studies (reviews, book reviews, etc.) and non-English, n = 13; study population not young and middle-aged adults with hypertension, n = 35; unrelated to topic, n = 106; and study only reported current status of sedentary behavior, n = 9), and 8 documents were included [ 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 ]. The steps of the literature search are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…After searching, a total of eight SB studies on young and middle-aged adults with hypertension were included, with the highest number of studies concentrated in stage 1. Out of all the included studies, 37.5% were from the United States, with three articles written by Gibbs [ 33 , 34 , 35 ]. Six studies focused on subjects with prehypertension, hypertension stage 1, and hypertension stage 2.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, an increase in PWV has also been observed in at-risk middle-aged adults during a simulated seated workday (total sitting time: >7 h) ( Alansare et al, 2020 ). These sitting-induced effects on PWV have been reported in young healthy adults ( Evans et al, 2019 ), overweight/obese adults ( Credeur et al, 2019 ) and middle-aged at-risk adults (overweight/obese, hypertensive) ( Alansare et al, 2020 ), highlighting that sitting can have broader effects on vascular health beyond lower limb arterial function. However, similar to FMD findings, there are inconsistencies across the literature with some studies reporting that PWV remains unaltered following uninterrupted prolonged sitting ( Kowalsky et al, 2019 ; Perdomo et al, 2019 ; Tremblay et al, 2019 ; Caldwell et al, 2020 ; Headid et al, 2020 ).…”
Section: Acute Effects Of Physical Inactivity On Vascular Function In...mentioning
confidence: 95%
“…Recent studies suggest that sitting (3 h) can negatively impact aortic stiffness in young adults as indicated by an increase in pulse wave velocity (PWV) (~0.35 m•s −1 ) (Credeur et al, 2019;Evans et al, 2019), which is the gold standard measure of arterial stiffness (Townsend 2016). Likewise, an increase in PWV has also been observed in at-risk middle-aged adults during a simulated seated workday (total sitting time: >7 h) (Alansare et al, 2020). These sitting-induced effects on PWV have been reported in young healthy adults (Evans et al, 2019), overweight/obese adults (Credeur et al, 2019) and middle-aged at-risk adults (overweight/obese, hypertensive) (Alansare et al, 2020), highlighting that sitting can have broader effects on vascular health beyond lower limb arterial function.…”
Section: Arterial Stiffnessmentioning
confidence: 99%